Leadership by the numbers - Lopp, Michael (O'Reilly Media, Inc., 2018)
A series of simple numbers can represent a useful and memorable corpus of hard-earned leadership experience. This video will succinctly explain essential leadership lessons that you can either heed or simply wait to experience.
Online resource; Title from title screen (viewed June 25, 2018)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos